2001
DOI: 10.1161/hc3801.097806
|View full text |Cite
|
Sign up to set email alerts
|

Improved Arterial Compliance by a Novel Advanced Glycation End-Product Crosslink Breaker

Abstract: Background-Arterial stiffening with increased pulse pressure is a leading risk factor for cardiovascular disease in the elderly. We tested whether ALT-711, a novel nonenzymatic breaker of advanced glycation end-product crosslinks, selectively improves arterial compliance and lowers pulse pressure in older individuals with vascular stiffening. Methods and Results-Nine US centers recruited and randomly assigned subjects with resting arterial pulse pressures Ͼ60 mm Hg and systolic pressures Ͼ140 mm Hg to once-dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
428
0
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 649 publications
(451 citation statements)
references
References 42 publications
13
428
0
10
Order By: Relevance
“…Interestingly, in elderly subjects and in animal models of ageing and diabetes, collagen cross-linking breakers have been shown to reduce stiffness of the heart, the large arteries and the kidneys. [39][40][41] This study has certain limitations. In particular, treatments were not standardized, and the differences and relationships found here may be due either to the effect of treatment or to its underlying indications.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, in elderly subjects and in animal models of ageing and diabetes, collagen cross-linking breakers have been shown to reduce stiffness of the heart, the large arteries and the kidneys. [39][40][41] This study has certain limitations. In particular, treatments were not standardized, and the differences and relationships found here may be due either to the effect of treatment or to its underlying indications.…”
Section: Discussionmentioning
confidence: 95%
“…The prevention or decrease of glycation and glycation-induced tissue damage could be possible therapeutic strategies for the treatment of diabetic neuropathy [39,40]. Recent clinical studies have shown that AGE breakers, including ALT-711 and alagebrium, may be able to decrease the adverse vascular effects of glycation with few side effects [41][42][43], although no benefits have been demonstrated in the area of neuropathy. The inhibition of pathological responses mediated by AGEs may have therapeutic potential for diabetic neuropathy, although the RAGE-mediated molecular mechanisms need to be explored in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end products can form crosslinks in and between the arterial pressure load-bearing elements of the arterial wall, thereby increasing arterial stiffness, and accordingly, the glycation crosslink breaker Alagebrium (formerly known as ALT-711) reduces arterial stiffness. 48 No earlier studies have examined whether the relationship between the MetS and arterial stiffness was mediated by ED, as estimated by brachial flow-mediated dilation. In our study, brachial flowmediated vasodilatation did not mediate the association between the MetS and femoral arterial stiffness, whereas it did in the brachial artery.…”
Section: Discussionmentioning
confidence: 99%